From strike-slip to reverse reactivation: The Crevillente Fault System and seismicity in the Bullas-Mula area (Betic Cordillera, SE Spain) - Carlos Sanz de Galdeano Equiza; Vicenta María Elisa Buforn Peiró (Geologica Acta, 2005)
Several major N80ºE faults occur in the Bullas-Mula area (SE Spain). These faults and the numerous thrust slices of the Sierra de Ricote can be related to the movements of the Crevillente (or Cadiz-Alicante) fault system, which causes the westward displacement of the Betic Internal Zone and part of the External Zone. These faults moved with dextral strike-slip from Late Burdigalian to Early Tortonian. From this time on, the σ1 position changed from a WNW-ESE direction to approximately N-S, giving rise to movements with a new reverse character. The focal mechanisms of the 1999 Mula earthquakes indicate a N80ºE nodal plane, and their pressure axes also coincide with the σ1 direction existing from the Late Miocene and deduced from mesotectonic analysis at many points of the region. There is also good coincidence between their epicentral position and the fault traces. The Bullas earthquakes that occurred in 2002 are not directly related to the Crevillente faults, although their stress-pressure axes coincide with the σ1 direction reported there.